'We won't let Brussels dictate us': Eurosceptic populism in Hungary and Poland. Issue 1 (1st January 2021) - Csehi, Robert; Zgut, Edit
ABSTRACT: As a result of various crises, the European Union (EU) witnessed the rise of Eurosceptic and/or populist parties in its member states. However, the link between Euroscepticism and populism remains under-theorized, and the East-Central European (ECE) region is still surprisingly under-studied. This paper aims to fill these gaps by studying the development of Eurosceptic populist narratives in Hungary and Poland. Connecting the literature on Euroscepticism and the ideational approach to populism, it is shown through Orbán's and Kaczyński's discourses how (1) the EU is equated with 'the corrupt elite' that stands in conflict with 'the pure people', the Hungarians and Poles, and (2) how the EU is claimed to act against the notion of popular sovereignty. While the article highlights differences between the Eurosceptic populist narratives of the two party leaders, a politically driven 'anti-imperialist' theme prevails in both cases, which differentiates them from their Western-European counterparts as well.